Factors influencing turnover intention among registered nurses in Thailand: a preliminary study - Posai, Vachira; Jitpanya, Chanokporn; Srisintorn, Wisarut; Thongsuksai, Paramee (Chulalongkorn Medical Journal, 2025)
Background: The current nursing shortage poses a major challenge for healthcare systems. Understanding the predictors of turnover intention is essential for establishing effective retention strategies. Objectives: This study examined demographic and psychological factors associated with turnover intention among nurses, focusing on burnout, emotional labor, effort–reward imbalance, practice environment, work– family conflict, and work engagement, with particular attention to age-related differences. Methods: The study used data from 1,005 nurses at two public hospitals in Thailand. Validated instruments included the Burnout Assessment Tool, Emotional Labor Scale, Effort–Reward Imbalance Questionnaire, Practice Environment Scale of the Nursing Work Index, Utrecht Work Engagement Scale, Work–Family Conflict Scale, and Turnover Intention Scale. Results: Younger, single, early-career, lower-income, inpatient nurses reported higher turnover intention, while having children appeared protective. Burnout, work–family conflict, effort–reward imbalance, unfavorable practice environments, and particularly low work engagement were the strongest predictors. Severe work–family conflict (odds ratio (OR) up to 15.73) and low engagement (OR up to 57.72) indicated particularly high risk. Age-stratified analyses revealed consistent effects of burnout, effort–reward imbalance, and unfavorable environments across age groups, although younger nurses were more susceptible to severe work–family conflict. Gender, education level, and emotional labor were not significant predictors. Conclusion: Effective retention strategies should prioritize enhancing engagement, reducing burnout, supporting work–family balance, and improving practice environments. Age-specific interventions are also necessary, as younger nurses are particularly affected by work–family conflict and effort–reward challenges.